Role of Groin Flap in Acute Hand Injuries - Rajinder Singh Thind; Ajaipal Singh (Indian Journal of Plastic Surgery)
The clinical experience of resurfacing acute hand injuries requiring full thickness cover in a series of 25 cases with groin flap has been presented. The anatomical basis of this unique and versatile flap has been discussed and its special merits have been brought out. We recommend the use of this flap as an emergency procedure in cases of acute hand trauma in view of its suitability speed, safety, adaptability and dexetrity.